2002
DOI: 10.1038/sj.ejcn.1601337
|View full text |Cite
|
Sign up to set email alerts
|

The impact on eating habits of temporary translocation from a Mediterranean to a Northern European environment

Abstract: Objective: To assess the effect of temporary translocation from a Mediterranean to a Northern European environment on the eating habits of a group of foreign students. Design: Cross-sectional survey of eating habits before and after moving from Greece to Glasgow, Scotland. Setting: University of Glasgow. Subjects: Eighty post-graduate Greek students. Interventions: A self-administered questionnaire comprising of three major sections: (1) general eating habits; (2) frequency of eating selected food items; (3) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
64
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 18 publications
11
64
0
4
Order By: Relevance
“…We demonstrated that household size was related to VI as previously reported by (Papadaki and Scott, 2002). Men living with someone had a higher intake than those living On the other hand, subjects from city areas had a higher VI compared with those living in metropolitan or town-rural areas.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We demonstrated that household size was related to VI as previously reported by (Papadaki and Scott, 2002). Men living with someone had a higher intake than those living On the other hand, subjects from city areas had a higher VI compared with those living in metropolitan or town-rural areas.…”
Section: Discussionsupporting
confidence: 70%
“…Our findings suggest that in the youngest and oldest age groups, especially for women, educational initiatives that aim to increase VI should include such strategies as increasing availability of vegetables in cafeterias and restaurants where they usually have lunch, furthermore, food price must be taken into consideration. Other authors found that subjects in their twenties reported low VI because of lack of time to cook vegetables or living alone for the first time and not having the skills to prepare vegetables dishes (Papadaki and Scott, 2002;Larson et al, 2006). We also found other unhealthy behaviors that were negatively correlated with VI in each age group.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…There are a fewer studies investigating the effect of temporary migration on eating habits. Studies of international students, among others, suggest that even a short term migration can result in significant and often undesirable changes in eating patterns (Kremmyda et al, 2008;Papadaki and Scott, 2002;Perez-Cueto et al, 2009;Wandel et al, 2008). The process which a minority group adopts the dietary practice of the host country is called dietary acculturation and can be multidimensional, dynamic and complex (Satia-Abouta et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…(19). Chesta et al (30) afirmaron que el crecimiento físico es un "espejo" de las condiciones sociales de la población y sugiere que los programas de intervención deberían incluir también a poblaciones en riesgo social.…”
Section: Perspectiva Teórico-metodológicaunclassified